PERLINDUNGAN HUKUM TERHADAP ANAK YANG KEHILANGAN ORANG TUA AKIBAT PANDEMI COVID-19 - Kayowuan Lewoleba, Kayus (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This article discusses one of the impacts of a serious problem that has hit the world, namely the Covid-19 pandemic, the impact of which is extraordinary, hundreds of thousands of people have lost their lives as a result of this terrible pandemic. Indonesia is one of the countries that has suffered enormous losses from the loss of human life and the collapse of the Indonesian economy. Apart from the loss of human life, other sectors such as the domestic and global economy have experienced destruction due to the impact of restrictions on social activities which have brought several economic sectors to a halt. The impact of this pandemic has forced many children in various parts of the world to lose their parents, they experience suffering and sorrow because they have lost the people they took refuge in. They are forced to live a life without their loved ones, they are forced to work to survive, and live a new life with all kinds of risks that they have to face, such as the potential for vulnerability, to experience various forms of violence from people around them who don't care about them. child's condition. The loss of the main guardian, namely parents or grandparents, puts children's future at risk. Without the presence of a guardian, children will have difficulty meeting their needs for clothing, food and shelter independently. Not only that, they are also threatened with losing the opportunity to continue the education they are currently receiving. Children's mental development is disrupted because they lose someone who always gives them attention and affection. Apart from that, they will also be vulnerable to child marriage, child trafficking and other acts of violence and crime. This research is normative legal research with an analytical descriptive approach